Crosswind and Vortex Usages for Electricity Production Enhancement of Solar Updraft Tower - Amnart Boonloi; Anan Sudsanguan; Withada Jedsadaratanachai (Modelling and Simulation in Engineering, 2024)
This research presents an improvement to the traditional solar updraft tower, which relies solely on solar energy and cannot operate continuously throughout the day. The enhancement involves a hybrid energy approach by installing a vortex generator at the top of the tower to convert crosswinds into a vortex flow at the chimney’s top. This modification induces an updraft within the tower, enabling it to generate electricity continuously, even at night when there is no sunlight. The aim is to enable the solar updraft tower to harness crosswind energy without altering the tower’s main structure. This involves developing a vortex generator from a unidirectional wind intake design to a three‐directional intake, enhancing the feasibility of commercial installation. Additionally, various designs and heights of vortex generators were developed, considering different crosswind speeds (2, 4, 6, and 8 m/s). The research utilizes the finite element method, along with real model construction, to validate the reliability of the study’s findings. The results indicate that the updraft speed is directly proportional to the crosswind speed. From a physical standpoint, the vortex generator with a height equal to D produced the best results in all experiments. The square, cylindrical, and diffuser shapes increased the wind speed inside the chimney by 60%, 41%, and 48%, respectively. These results from various shapes provide effective design and development guidelines for the future commercial use of vortex generators.
Keywords: Solar Energy Systems and Technologies; Building Energy and Comfort Optimization; Wind and Air Flow Studies